RNA regulation of inflammatory responses in glia and its potential as a therapeutic target in central nervous system disorders. Issue 3 (15th November 2022) - Guha, Abhishek; Husain, Mohammed Amir; Si, Ying; Nabors, L. Burt; Filippova, Natalia; Promer, Grace; Smith, Reed; King, Peter H.
Abstract: A major hallmark of neuroinflammation is the activation of microglia and astrocytes with the induction of inflammatory mediators such as IL‐1β, TNF‐α, iNOS, and IL‐6. Neuroinflammation contributes to disease progression in a plethora of neurological disorders ranging from acute CNS trauma to chronic neurodegenerative disease. Posttranscriptional pathways of mRNA stability and translational efficiency are major drivers for the expression of these inflammatory mediators. A common element in this level of regulation centers around the adenine‐ and uridine‐rich element (ARE) which is present in the 3′ untranslated region (UTR) of the mRNAs encoding these inflammatory mediators. (ARE)‐binding proteins (AUBPs) such as Human antigen R (HuR), Tristetraprolin (TTP) and KH‐ type splicing regulatory protein (KSRP) are key nodes for directing these posttranscriptional pathways and either promote (HuR) or suppress (TTP and KSRP) glial production of inflammatory mediators. This review will discuss basic concepts of ARE‐mediated RNA regulation and its impact on glial‐driven neuroinflammatory diseases. We will discuss strategies to target this novel level of gene regulation for therapeutic effect and review exciting preliminary studies that underscore its potential for treating neurological disorders. Main Point: Review mechanisms of RNA regulation of glial neuroinflammatory responses